Legal Inforcement for Highway Management in Lao PDR: A case Study of Highway Management from Vientiane Capital to Vangvieng District Viantiane Province - xayavong, somkhuan; BOUNPHONG, Xay; LATTANASOUVANNAPHONH, Champa; INTHASUPHANH, Vanxay; OUTHAI, Ling (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The objectives of this study are to: 1) investigate the management status of the expressway from Vientiane Capital to Vangvieng District, Vientiane Province; 2) assess drivers' awareness of the regulations on expressway management in the Lao PDR; and 3) determine guidelines for the sustainable management of the Vientiane Capital to Vangvieng District expressway. Data were collected using structured interviews and 385 survey questionnaires, and analyzed using the SPSS software (version 26). The findings revealed that: Regarding the expressway management status, the decentralization of management is not yet aligned with the actual environment, vehicles using the expressway do not consistently meet the specified technical standards, traffic regulation enforcement on the expressway remains lax, and the participation of relevant sectors and the public in preserving the expressway is still limited, leading to various negative issues. As for drivers' awareness of the expressway management regulations, the overall awareness was at a low level (=2.26 and SD=0.76 ), which includes the following aspects: awareness of the mode of expressway management is moderately aware (=2.63 and SD=1.02), followed by awareness of toll collection, rights and obligations of expressway operators are at a low level (=2.45 and SD=0.78), Secondly, the awareness of the overall principles of expressway management was low (=2.18 and SD=0.73), while the awareness of the prohibitions in expressway management was low (=2.08 and SD=0.66) and the awareness of the regulations on the use of expressways was also at a low level (=1.94 and SD=0.63). Therefore, the expressway management guidelines to ensure sustainability by reviewing the implementation of expressway management regulations in line with the current situation in Singapore, developing the mode of dissemination of expressway regulations to keep up with the era of online social media, and opening up to all sectors and citizens to participate more in expressway management.